2004
DOI: 10.1016/j.neuron.2004.10.028
|View full text |Cite
|
Sign up to set email alerts
|

The Translational Repressor Pumilio Regulates Presynaptic Morphology and Controls Postsynaptic Accumulation of Translation Factor eIF-4E

Abstract: Translational repression by Drosophila Pumilio (Pum) protein controls posterior patterning during embryonic development. Here, we show that Pum is an important mediator of synaptic growth and plasticity at the neuromuscular junction (NMJ). Pum is localized to the postsynaptic side of the NMJ in third instar larvae and is also expressed in larval neurons. Neuronal Pum regulates synaptic growth. In its absence, NMJ boutons are larger and fewer in number, while Pum overexpression increases bouton number and decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
179
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(188 citation statements)
references
References 38 publications
8
179
1
Order By: Relevance
“…Our work also suggests an interesting mechanism of translational control within transport particles (2,20). In Drosophila, Pum binds a series of transcripts, with one example being eIF4E (2, 4).…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Our work also suggests an interesting mechanism of translational control within transport particles (2,20). In Drosophila, Pum binds a series of transcripts, with one example being eIF4E (2, 4).…”
Section: Resultsmentioning
confidence: 73%
“…In Drosophila, Pum binds a series of transcripts, with one example being eIF4E (2, 4). eIF4E has been shown to be part of translational particles near synapses (2). Knock-down of Pum led to an increase in eIF4E, and it was concluded that Pum was negatively regulating the translation of eIF4E.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Drosophila Pum and mammalian Pumilio 2 proteins control the abundance of eIF-4E mRNA by binding its 3'UTR and mediating its decay. 26,27 However, recently mammalian Pumilio 2 was shown to interfere with translation control through a non-decay pathway by competing with eIF-4E protein for access to the 7-methyl guanosine cap and repressing the initiation of translation by outcompeting eIF-4E, thereby preventing formation of the initiation complex. 28 Hence, certain Pumilio proteins appear to play a role in the initiation of translation by controlling eIF-4E.…”
Section: Pumilio Puf Domain Rna-binding Proteins In Arabidopsismentioning
confidence: 99%
“…It is also possible that APUM23 interacts with translation initiation factors, such as eIF-4E, and mediates translation control, as do mammalian Puf proteins, 28 or it may bind to the 3'UTR of eIF-4E mRNA to control its translation. 26,27 The increased sensitivity of apum23-1 to cycloheximide, a eukaryotic protein synthesis inhibitor and its resistance to the antibiotic streptomycin, argue in favor of the involvement of APUM23 in the control of translation and ribosome biogenesis. Ribosomal proteins and rRNA together constitute the structural components of the ribosomes.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%